Pengaruh Teman Sebaya, Pendidikan Karakter, Keterampilan Belajar, Pemberian Reward Dan Interaksi Sosial Keluarga Terhadap Prestasi Belajar Siswa Kelas VIII Di MTsN 06 Padang - Mutiara, Ica -; Stevani, Stevani; Dahen, Lovelly Dwinda (Jurnal Horizon Pendidikan, 2022)
This study aims to analyze the sampling technique was Proportional Random Sampling with a total sample of 113 students. The results showed that: 1), peers have a significant effect on learning achievement. Where indicated by the coefficient value of 0.336. This coefficient value is significant because the t-count is 3,477 > t-table is 1,65909. 2), character education has a significant effect on learning achievement. Where indicated by the coefficient value of 0.326. This coefficient value is significant because the value of t-count is 3.153 > t-table of 1.65909. 3), learning skills have a significant effect on learning achievement. Where indicated by the coefficient value of 0.180. This coefficient valueis significant because the value of t-count is 2.246 > t-table of 1.65909. 4), giving rewards have a significant effect on learning achievement. Where indicated by the coefficient value of 0.206. This coefficient value is significant because the value of t-count is 2,929 > t-table of 1,65909. 5), social family interactions have a significant effect on learning achievement. Where indicated by the coefficient value of 0.640. This coefficient value is significant because the value of t-count is 5,002 > t-table of 1,65909. 6), character education, learning skills, giving rewards, and social family interaction together have a significant effect on the learning achievement. Where obtained by the value of F-count 142.226 > F-table 2.30 with a significant level of 0.000 <= 0.05. This means that Ha is accepted and H0 is rejectedKeywords: Peers,Character Education, Learning Skills, Giving Rewards, And Social Family Interaction On Student Achievement.